Plankton biomass and water quality of Lake Ahémé in south-west of Benin - Boukari, Ousmane Touré; DOVONOU, Flavien; ABOU, YOUSSOUF; MAMA, DAOUDA; CHOUTI, WARIS KEWOUYEMI (My University, 2022)
The study concerns the evaluation of the water quality of Lake Ahémé by plankton communities and was initiated following the sanitation works carried out by the Agency for the Integrated Development of the Economic Zone of Lake Ahémé and its Channels (ADELAC). The work was done in July 2020 on four defined points on the lake. The inventory and the evaluation of the biomass were carried out thanks to microscopic observations and identification of taxa's keys. The species inventory revealed 22 phytoplankton species belonging to 04 classes and 13 zooplankton species divided into 03 groups. The evaluation of the phytoplankton biomass shows that Diatomophyceae have the highest density (862 individuals/L) and Chlorophyceae the lowest (3 individuals/L). As for the zooplankton, Copepods are the most abundant (118 individuals/L) and Cladocerans the least (3 individuals/L). The planktonic index (3 - 15.25) showed that the lake is oligotrophic at the four sampled sites. According to the water quality grid, oligotrophy reflects good water quality. Compared to previous studies, the water quality has improved following the sanitation operation. This progress must be preserved through actions to protect the lake.
Keywords: subsaharan Africa; Dahomey; microflora; water composition and quality; aquatic species